Joy in the Morning - Phororo, Hopolang (Book collections on Project MUSE., 2011)
Hopolang was sexually abused by a neighbor and for nineteen years she didnít divulge her experience because she feared that she would be blamed. In the first edition of ëJoy Comes in the Morningí she shared her battle to regain her self-confidence and self-esteem by running into the arms of the One who can heal - God. Through poems, she expresses emotions, such as confusion, pain, fear, betrayal, guilt, regret, approval, self-pity, mistrust and forgiveness that she had to work through. In this revised edition of ëJoy Comes in the Morningí, Hopolang recounts how she overcame, not only the traum.